PENGARUH DESTINATION IMAGE DAN SUBJECTIVE NORM TERHADAP BIAT BERKUNJUNG WISATA SUNAN AMPEL SURABAYA - Ramadhani, Sintesa Aulia; Kurniawati, Masmira (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2019)
One of the attractions in East Java that is visited by many tourists is the religious tourism area of the Sunan Ampel Mosque. The enchantment of culture, art and history contained in the Sunan Ampel Mosque has a special attraction for tourists. The 2014 data states that the tomb of Sunan Ampel in Surabaya became the most visited location of pilgrims, namely more than 1.9 million visits. Therefore, this study aims to determine the effect of destination and subjective norms on the intention to visit Sunan Ampel Religious tourism by using 100 samples where the sample criteria are at least 17 years old and have never visited Sunan Ampel religious tourism. This study uses SPSS 22. The results of the study concluded that destination image and subjective norm have a significant effect on the intention of visiting Sunan Ampel Religious tourism.Keywords: Image destination; Subjective norm; intention to visit